ANALISIS LAPORAN LABA RUGI PADA USAHA CATERING PT PENGEMBANGAN JAYA PAPUA - Meliany Efruan; Natalia Reyne Lumentah (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2018)
The aims of this research is to find out and know the financial condition of PT Pembangunan Jaya Papua. This research is a qualitative descriptive research. The data used are primary data in the form of interviews and secondary data in the form of financial statements of PT Pembangunan Jaya Papua. Data collection techniques in this study are through interviews, documentation and literature studies. To find out the financial condition of PT Pembangunan Jaya Papua, it is used a profitability ratio consisting of gross profit margin, net profit margin, ROE, and ROI. The results of this research indicate that (1) the gross profit margin of PT Pembangunan Jaya Papua for two years has not changed, namely by 46%. This ratio is considered good because it is greater than the industry average of 30%. (2) The net profit margin of PT Developera Jaya Papua for two years has not changed, namely by 14%. This ratio is considered unfavorable because it is below the industry average of 20%. (3) PT Pembangunan Jaya Papua's return on equity decreased from 42% in 2014 to 39% in 2015. This ratio was considered unfavorable because it experienced a decline from 2014 to 2015 and was below the industry average of 40 %. (4) PT Pembangunan Jaya Papua's return on investment has decreased from 2014 by 33% to 32% in 2015. This ratio is considered good because it is above the industry average of 30%